An insight into bacteriophages' response to various physical and chemical conditions: temperature, pH, salts - Auroni, Tabassum Tasnim; Islam, Md Deen; Khatun, Mst Salma; Monjur, Md Shifat E; Yasmin, Mahmuda; Ahsan, Chowdhury Rafiqul; Jamalunnessa, - (Dhaka University Journal of Biological Sciences, 2016)
Bacteriophages can survive under unfavorable conditions and their abilities of survivality are highly diversified. The influence of different physical and chemical conditions, such as temperature, pH and salts on the survivability of coliphages and shigaphages isolated from local clinical sewage samples have been summarized. Temperature at 45°C for 30 min caused 53.13% decrease in the number of coliphages but rather increased the number of shigaphages in present study. Temperature at 56°C for 30 min caused 91.41 and 100% fall in the number of coli- and shigaphages, respectively. pH 4 mediated 96.88% and pH 11 caused 100% decline in the number of plaques for coliphages. On the other hand, number of plaques of shigaphages was diminished by 100% at pH 4 and 91.67% at pH 11. MgCl2, MgSO4 and Na2SO4 salt solutions increased the number of coliphage plaques by 287.5, 125 and 37.5%. On the contrary, the decrease in the number of shigaphages was 79.31, 10.34 and 44.83%, respectively through the treatment. The various physical and chemical conditions investigated in this research have affected the test bacteriophages diversely. Temperature while applied at higher level (56ºC) affected the growth of both coliphages and shigaphages. Acidic and alkaline pH modified coli- and shigaphages' survivality and growth negatively. The three salts in question augmented the growth of isolated coliphages profoundly. However, the same three salts failed to do so for the isolated shigaphages. Dhaka Univ. J. Biol. Sci. 25(2): 185-194, 2016 (July)